The Contribution of Female Health to Economic Development - David E. Bloom; Michael Kuhn; Klaus Prettner (Institute for the Study of Labor (IZA), 2015)
We analyze the economic consequences for less developed countries of investing in female health. In so doing we introduce a novel micro-founded dynamic general equilibrium framework in which parents trade off the number of children against investments in their education and in which we allow for health-related gender differences in productivity. We show that better female health speeds up the demographic transition and thereby the take-off toward sustained economic growth. By contrast, male health improvements delay the transition and the take-off because ceteris paribus they raise fertility. According to our results, investing in female health is therefore an important lever for development policies. However, and without having to assume anti-female bias, we also show that households prefer male health improvements over female health improvements because they imply a larger static utility gain. This highlights the existence of a dynamic trade-off between the short-run interests of households and long-run development goals. Our numerical analysis shows that even small changes in female health can have a strong impact on the transition process to a higher income level in the long run. Our results are robust with regard to a number of extensions, most notably endogenous investment in health care.
Keywords: O11; I15; I25; J13; J16; 330; economic development; educational transition; female health; fertility transition; quality-quantity trade-off